Temperature, climate change, and fertility - Tamás Hajdu; Gábor Hajdu (Global Labor Organization (GLO), 2021)
This chapter reviews the empirical literature on the impacts of temperature and climate change on human pregnancies. The focus is on the quasi-experimental studies that use panel data, apply a fixed effect approach, and exploit the random year-to-year fluctuation in temperature. The insights that emerge from the review highlight that exposure to heat in the pre-conception period has detrimental impacts on fertility. In addition, heat during pregnancy increases pregnancy losses, leads to a reduction in gestational length, and lowers birth weight. Despite the growing empirical evidence on the subject, understanding the relationship between temperature and pregnancy-related outcomes is far from perfect. Importantly, the potential impacts of climate change are rarely quantified. The chapter outlines directions for future research.
Keywords: J13; Q54; 330; temperature; climate change; fertility; pregnancy; health at birth; birth weight; pregnancy loss